2021
DOI: 10.1186/s12884-021-03859-6
|View full text |Cite
|
Sign up to set email alerts
|

Primitive neuroectodermal tumor of the cervix diagnosed during pregnancy: a rare case report with discussion

Abstract: Background Primitive neuroectodermal tumor (PNET) is a relatively rare malignant small round cell tumor, and the occurrence of cervical PNET during pregnancy is extremely rare. Case presentation A case of pregnancy complicated by PNET at our hospital was reported. A 19-year-old pregnant woman presented to the hospital due to multiple instances of vaginal bleeding during the first and second trimesters. She was initially considered for threatened ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…A follow-up of 42 and 33 months, respectively, showed both patients to be alive after initial diagnosis. In addition to the reports of cervical PNET in pregnancy, Feng et al and Al-Nueimy et al also described one case each, found at 14 weeks of pregnancy and during cesarean section at term, respectively ( Al-Nueimy, 2014 ; Feng et al, 2021 ). Both patients presented with cervical masses of 3 cm × 3 cm and 6 cm × 4.5 cm, respectively.…”
Section: Discussionmentioning
confidence: 94%
“…A follow-up of 42 and 33 months, respectively, showed both patients to be alive after initial diagnosis. In addition to the reports of cervical PNET in pregnancy, Feng et al and Al-Nueimy et al also described one case each, found at 14 weeks of pregnancy and during cesarean section at term, respectively ( Al-Nueimy, 2014 ; Feng et al, 2021 ). Both patients presented with cervical masses of 3 cm × 3 cm and 6 cm × 4.5 cm, respectively.…”
Section: Discussionmentioning
confidence: 94%
“…It is a high-grade malignant tumor with early metastasis and an extremely poor prognosis. PNET can reportedly develop anywhere in the body, including the orbit, nasal cavity, mediastinum, stomach, bone, uterus, kidney, neck, chest, pancreas, gingiva, paraspinal region, ovaries, breast, testes, and thymus; 1 4 , 6 9 however, it is rarely found in the lung. Only 15 related cases were retrieved from the literature from 2012 to 2022 ( Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…As a member of the Ewing sarcoma family, PNET can be classified into central or peripheral subtypes, both of which can affect organs other than those in the neurological, soft tissue, and skeletal systems in children and adolescents. 1 4 The diagnosis of PNET largely depends on pathological and molecular examinations. Given the rarity and extremely poor prognosis of PNET with pulmonary invasiveness, 1 we believe that it is clinically valuable to report the clinical features, treatments, follow-up procedures, histological characteristics, and genomic variants of such cases to expand the knowledge of this disease.…”
Section: Introductionmentioning
confidence: 99%
“…Few conclusions can be drawn from case reports relating to cervical cancer of rare histology diagnosed during pregnancy. In decreasing frequency order, we retrieved cases about treating neuroendocrine carcinomas [97,113,120,121,[136][137][138][139][140][149][150][151][152][153][154], clear cell carcinomas [134,135,155], and sarcoma [98].…”
Section: Rare Histological Typesmentioning
confidence: 99%
“…Most patients diagnosed with neuroendocrine tumors at the first or early second trimester of pregnancy underwent termination of pregnancy [121,136,151,154] to prevent any delay in cancer management. Three out of fifteen patients were diagnosed with stage FIGO 2018 IVB disease and died within months after the diagnosis [137,150,152].…”
Section: Rare Histological Typesmentioning
confidence: 99%